Correlative Study Between Nutritional Status and Remission Outcome in Childhood Acute Lymphoblastic Leukemia in Dr. Soetomo General Hospital Surabaya - Asma' Athifah; Siti Nurul Hidayati; Sulistiawati Sulistiawati (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2019)
Introduction: The most common malignancy that is diagnosed in children is acute lymphoblastic leukemia. Undernourished children tend to have poorer long term survival. This descriptive analytic study is aimed towards analyzing the correlation between nutritional status at diagnosis and outcomes of induction phase therapy in childhood acute lymphoblastic leukemia at the Department of Pediatrics Dr. Soetomo General Hospital Surabaya in 2014.Methods: A cross-sectional method using the medical records of patients is used in this study. The nutritional statuses of patients are calculated using weight for length/height trough curves of WHO 2006 or CDC 2000.Results: The results show that from 45 children diagnosed with ALL, 53% are of the age ≤ 5 years old, with 58% males and 42% females. 13% of the patients are in the high risk group and 87% are in the standard risk group. Nutritional statuses of patients are 2% of them obese experienced remission after induction phase therapy, 56% normal with 80% of them experienced remission. 40% underweight with 89% of them experienced remission and 11% not experienced remission, 2% malnutrition and experienced remission. There is no correlation between the nutritional status of children with acute lymphoblastic leukemia with the outcome of induction phase (p = 0.798).Conclusion: In conclusion, there is no correlation between nutritional status and remission outcome of patients with ALL in the induction phase of therapy. However, high percentage of underweight patients shows nutrition needs special attention to improve therapy outcomes.